Comparative dynamic performance of hybrid absorption thermal batteries using H2O/1, 3-dimethylimidazolium dimethylphosphate. (15th January 2021) - Wu, Wei; Ding, Zhixiong; Sui, Yunren; Leung, Michael
Highlights: H2 O/ionic liquid can effectively avoid crystallization problems of thermal battery. Compression-assisted absorption thermal battery enlarges concentration differences. Storage density is greatly increased from 110.3 to 199.2 kWh/m 3 by hybrid battery. Battery with discharging compression has the highest storage efficiency of 0.816. Discharging compression outperforms charging compression by 52% in storage density. Abstract: The basic absorption thermal energy storage cycle suffers from low energy storage efficiency and density, while the conventional H2 O/salt working fluids risk crystallization problems. To achieve crystallization-free thermal batteries with improved energy storage performance, a hybrid compression-assisted absorption thermal energy storage cycle using H2 O/1, 3-dimethylimidazolium dimethylphosphate is proposed. The fluid property is modeled using non-random two liquid equations and the hybrid cycle is modeled using heat/mass transfer/conservation equations; both models are validated against measurement data with good accuracies. The effect of pressure ratio on the transient behaviors and energy storage density/efficiency is investigated to characterize the performance enhancement. Besides, different hybrid cycles are compared with the basic cycle to identify the best-performing thermal battery. Results show that, with both generation and absorption enhancement, the concentration difference is significantly enlarged from 0.230 to 0.480 by the hybrid cycle with a pressure ratio of 2.0. Meanwhile, with energy storage efficiencies maintained at 0.715–0.794, the energy storage density is effectively increased from 110.3 to 199.2 kWh/m 3 . Through valve switching, three hybrid cycles are realized, i.e., hybrid cycle with charging/discharging compression, hybrid cycle with charging compression, and hybrid cycle with discharging compression. Comparisons indicate that the hybrid cycle with discharging compression is the most energy-efficient, with the highest energy storage efficiency of 0.816, compared to 0.794 of the hybrid cycle with charging/discharging compression and 0.790 of the hybrid cycle with charging compression. In terms of energy storage density, the hybrid cycle with discharging compression performs quite close to the hybrid cycle with charging/discharging compression, only slightly lower by 1.6–4.3%. However, compared to the hybrid cycle with charging compression, the energy storage density of the hybrid cycle with discharging compression is significantly enhanced by 11.4–52.0%. In summary, the hybrid cycle with discharging compression is the best cycle comprehensively considering the energy storage efficiency and density. This study aims to provide theoretical supports and suggestions for the development of advanced thermal battery cycles.